2017
DOI: 10.18203/2349-3291.ijcp20164302
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical cord blood culture versus peripheral venous blood culture in early onset neonatal sepsis

Abstract: Background: Neonatal sepsis is a major cause of neonatal morbidity and mortality. Blood culture and sensitivity is gold standard for the diagnosis of neonatal sepsis. Low sensitivity of blood culture especially in newborn is due to small volume of blood sample collected from neonates and antibiotics given before sampling. The aim was to evaluate the use of umbilical cord blood culture in the diagnosis of early onset neonatal sepsis as compared to Peripheral vein blood culture. Methods: Eighty neonates with two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
2
4
0
Order By: Relevance
“…While other risk factors did not show any statistically significant correlation with EONS with P>0.05. Similar findings were reported in other studies by Mandot et al, Dutta et al, Pramana et al[4][5][6]…”
supporting
confidence: 92%
“…While other risk factors did not show any statistically significant correlation with EONS with P>0.05. Similar findings were reported in other studies by Mandot et al, Dutta et al, Pramana et al[4][5][6]…”
supporting
confidence: 92%
“…21 Mandot and Gandhi had done a similar study which revealed that 23 babies out of 80 (30.6%) had positive sepsis screening. 22 In our study, 9% of the UCBC from newborns with suspected EONS had significant growth of organism consistent with EONS as compared to 7% by PVBC. About 5% of the newborns with suspected EONS had 23 Chacko and Sohi did a study on EONS in which 136 neonates with risk factors for EONS and the most common organism isolated was Pseudomonas (60%).…”
Section: Discussionmentioning
confidence: 45%
“…Several studies have unanimously declared that umbilical cord blood culture is a simple, painless and reliable approach for diagnosing EOS. Kalatia and Mandot introduced UCB culture as a useful method for the diagnosis of neonatal sepsis with an 80% susceptibility and 91.4% specificity (1). In the present study, UCB infections had a prevalence of 1.85%, and all the neonates with this infection had EOS manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal sepsis refers to a bacterial bloodstream infection presenting with systemic symptoms that is classified into two groups, including Early-Onset Sepsis (EOS) and Late-Onset Sepsis (LOS). EOS is usually caused by vertical transmission and appears during the first three days after childbirth, while horizontal transmission by hand/body contact or intra-venous catheters can lead to LOS within four to 28 days of birth (1). Despite the outstanding advances in neonatal medicine, sepsis remains a leading cause of death, and approximately five million newborns die around the world every year as a result of these infections (2).…”
Section: Introductionmentioning
confidence: 99%